Evaluation of Women's Knowledge and Personal Preference about The Place of Delivery in Baghdad City - Sameen, entsar; Abdul Sattar, Khalida (Iraqi National Journal of Nursing Specialties, 2017)
Objective: The study aim to evaluate of women's knowledge and personal preference about the placeof delivery in Baghdad CityMethodology:descriptive study conducted in baghdad city on the mothers for the period from the 14th of December,2015 to the 14th of April 2016. The sample of study included 500 mothers who were attending toprimary health care centers have been chosen sample of 26 primary health care center by a multi-stageSimple random sampling Data was collected through a constructed questionnaire, validity Data wasanalyzed by using of descriptive and inferential data analysis methods .Results: The results indicated that approximately (29.4%) of the mothers in the age group (20-24) andthe average age of the mothers (29.97) a year and the majority of the study sample housewives andapproximately (93.4%) of the level social and economic of Low & Moderate that ( 24.4%) womenamong the 500 chosen to the home as a place to give birth, while the majority (52.6%) chose thehospital as a place of birth for security reasons, safety, and the advice of doctors or medical The chosenof the house was for privacy reasons and social attribution.Third of the mothers do not have knowledgeof pregnancy at risk and symptoms of delivery.Recommendations: Improve the maternity services at hospital to be ofhigh quality care safe healthy & comfortable place for delivery.the obstetricians should ask allwomen about preferred place of delivery & try to help them according to their condition and directthem to take right choice